EFFECT OF ZINC FERTILIZATION ON GROWTH, YIELD AND QUALITY OF FODDER MAIZE (Zea mays L.) - A. MADHAVI; M. VENKATESWARLU, CH. RAMAKRISHNA, A. MADHAVI LATA, B. MURALI (The Journal of Research, PJTSAU, 2023)
A field experiment was conducted on sandy clay loam soil at College farm, College of Agriculture, Rajendranagar, Hyderabad during rabi, 2019-20 and 2020-21 on “Effect of zinc fertilization on growth, yield and quality of fodder maize (Zea mays L.)”. The treatment comprised of soil and foliar applications of zinc viz., Recommended dose of fertilizers (RDF) alone (120 kg N - 50 kg P 2 O5 - 40 kg K 2 O ha-1) without zinc application (T1), Soil application of 15 kg ZnSO 4 ha-1 (T2), Soil application of 25 kg ZnSO4 ha-1 (T3), Foliar spray of 1% ZnSO4 at 20 and 45 days (T4) and Foliar spray of 1% ZnSO4 at 20, 45 and 60 days (T5). The five treatments were laid out in randomized block design with four replications. A fodder maize variety, African tall was used by adopting a spacing of 30×10 cm. The recommended dose of fertilizers was applied to all the treatments. The experimental soil was moderately alkaline in reaction, low in organic carbon, available nitrogen (N) as well as low in available zinc (Zn), medium in available phosphorous (P2O5) and high in available potassium (K2O). It is concluded that among different zinc fertilization treatments studied in fodder maize, Foliar spray of 1% ZnSO4 at 20, 45 and 60 days with RDF (T5) recorded significantly higher plant height, leaf to stem ratio, dry matter, green fodder yield, crude protein and other quality parameters proved better in registering higher zinc concentration in green fodder and was found economically viable with higher net returns, followed by T 4. Lowest was recorded with no Zn application (T1) in both the years of study. Overall, our study suggest that zinc fertilization of maize through soil and/or foliar spray can enhance not only fodder productivity and also improve quality of fodder maize in Southern Telangana zone elsewhere under similar agro-climatic conditions.